2007
DOI: 10.1128/jb.01685-06
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Regulation of Biofilm Formation and Swarming Motility byPseudomonas aeruginosaPA14

Abstract: We previously reported that SadB, a protein of unknown function, is required for an early step in biofilm formation by the opportunistic pathogen Pseudomonas aeruginosa. Here we report that a mutation in sadB also results in increased swarming compared to the wild-type strain. Our data are consistent with a model in which SadB inversely regulates biofilm formation and swarming motility via its ability both to modulate flagellar reversals in a viscosity-dependent fashion and to influence the production of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
273
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(294 citation statements)
references
References 51 publications
10
273
1
3
Order By: Relevance
“…The mutant was also deficient in polysaccharide production and displayed altered reversal patterns while swimming in high-viscosity medium, two behaviors proposed to influence biofilm formation and swarming motility. Similarly, SadB was found to inversely regulate biofilm formation and swarming motility via its ability to both modulate flagellar reversals in a viscosity-dependent fashion and influence the production of the Pel exopolysaccharide (19,20). The role of SadB in the transition to irreversible attachment was further confirmed by microscopic examination that revealed an increased number of sadB mutant cells adhering via the cell pole.…”
Section: Let's Make It Permanent: Transition To Irreversible Attachmentmentioning
confidence: 60%
“…The mutant was also deficient in polysaccharide production and displayed altered reversal patterns while swimming in high-viscosity medium, two behaviors proposed to influence biofilm formation and swarming motility. Similarly, SadB was found to inversely regulate biofilm formation and swarming motility via its ability to both modulate flagellar reversals in a viscosity-dependent fashion and influence the production of the Pel exopolysaccharide (19,20). The role of SadB in the transition to irreversible attachment was further confirmed by microscopic examination that revealed an increased number of sadB mutant cells adhering via the cell pole.…”
Section: Let's Make It Permanent: Transition To Irreversible Attachmentmentioning
confidence: 60%
“…Cumulative reports in the literature have revealed trends in the relationships between a strain's matrix production during colony growth, ability to form a biofilm at the air-liquid interface of a static culture (pellicle), and capacity for swarming (motility over semisolid surfaces) (24,25,27,28). We note that the Δphz mutant is unusual in this context because it shows increased matrix production in the colony morphology assay but also exhibits swarming behavior comparable to that of the WT in motility assays; typically, P. aeruginosa mutants with altered c-di-GMP signaling show an inverse correlation between matrix production and swarming.…”
Section: δPa14_07500 and δPhz Mutants Exhibit Similar Phenotypes In Amentioning
confidence: 99%
“…Lastly, SadB is predicted to be involved in the transmission of the signal to Pel machinery and components of the chemotaxis machinery in order to regulate biofilm formation and swarming motility (Caiazza, 2004(Caiazza, , 2007. These findings suggest that the nearly 40 P. aeruginosa DGC/PDE enzymes generate specific phenotypic outputs by altering subcellular c-di-GMP pools.…”
Section: P Aeruginosa Environmental Lifestyle and Virulence 59mentioning
confidence: 89%
“…SadB/C/BifA pathway Studies performed by George O'Toole's group have identified several factors that are involved in inversely regulating surface-associated behaviors (Caiazza, 2004(Caiazza, , 2007Kuchma and O'Toole, 2007;. Previously, a genetic screen identified surface attachment-defective (sad) mutants of P. aeruginosa PA14, defined by their inability to form biofilms in a microtiter dish biofilm assay (O'Toole, 1998(O'Toole, , 2000.…”
Section: P Aeruginosa Environmental Lifestyle and Virulence 59mentioning
confidence: 99%